Reference signal received power (RSRP)-based localisation using 5G signals - Shang, Pengfei (Nanyang Technological University, 2022)
With the development of wireless communication technology and Internet of Things, the demand for location-based services is increasing. Location-based service has been used in warehouse for asset localization, intelligent city construction, fire and earthquake disaster area emergency personnel positioning and so on. However, due to the occlusion of buildings and other reasons, GPS signals cannot achieve high-precision positioning, especially in indoor environment. Therefore high-precision positioning system and positioning scheme have become a research hotspot in the field of location services. The fifth generation (5G) wireless network allows not only for a tremendous increase in capacity for communication but also opens new opportunities for high accuracy positioning of user equipment. Reference Signal Received Power (RSRP) measurements are one of the supported positioning methods for 5G Orthogonal Frequency Division Multiplexing (OFDM) system. In this dissertation, a RSRP-based positioning method will be investigated and developed. The designed positioning method is based on fingerprint which uses a database-based mapping solution and build up a signal propagation model to characterize the relations between transmission distance and received signal strength.